High Oxygen Treatments Enhance the Contents of Phenolic Compound and Ganoderic Acid, and the Antioxidant and DNA Damage Protective Activities of Ganoderma lingzhi Fruiting Body - Dong, Qingying; Li, Yueyue; Liu, Gaoqiang; Zhang, Zhiwei; Zhou, Huabin; Yang, Hailong (Frontiers in Microbiology, 2019)
Ganoderma lingzhi is a famous medicinal mushroom used as Chinese medicine or functional food, and has been accepted across the globe. It is important to enhance the contents of bioactive compounds which in turn improve the quality and biological activity of G. lingzhi fruiting body. In this work, freshly harvested G. lingzhi fruiting bodies were treated continuously with air or with 60 % and 80 % oxygen for 6 d. Samples were collected and determined initially and at 1-day interval during treatment. A high total ganoderic acid content of 29.44 g kg-1 was obtained in samples treated by 60 % oxygen at day 3. qRT-PCR and HPLC analysis showed that the expression levels of hydroxymethylglutaryl-CoA synthase, squalene synthase and oxidosqualene cyclase genes were substantially increased, resulting in the increase of ganoderic acid A, B, C2, and ganoderenic acid B. The scavenging activities with 1,1-diphenyl-2-picrylhydrazyl radical, 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) radical, hydroxyl radical and superoxide radical and DNA damage protective activity were also enhanced by high oxygen treatment. The results of this work provided a potential method to enhance the active metabolites synthesis in the fruiting body of G. lingzhi.